PENGARUH PENGEMBANGAN KOMPETENSI DAN BUDAYA KERJA TERHADAP KEPUASAN KERJA MELALUI KEPERCAYAAN DIRI PEGAWAI PPSDM KEMENTERIAN ATR/BPN - Hernawo, Toto; Martono, Besar Agung (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
In the era of globalization and increasingly fierce competition, it is important for organizations to develop the competencies of their employees so they can compete and achieve organizational goals more effectively. The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) has a Human Resources Development Center (PPSDM) which is responsible for the task of developing employee competency through competency development programs that are effective and relevant to employee needs, so that employees are expected to have adequate competency. as expected. This research aims to explore the influence of the competency development program on the self-confidence of PPSDM Ministry ATR/BPN employees, as well as its impact on their job satisfaction. In addition, this research will also examine whether work culture moderates the relationship between competency development and self-confidence, as well as its impact on employee job satisfaction. This research was conducted at the Center for Human Resources Development (PPSDM) of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) with the research sample using the entire population of PPSDM Ministry of ATR/BPN civil servant employees totaling 55 people. The data collection technique was carried out using a questionnaire, four rating scales from strongly disagree to strongly agree. The research was conducted quantitatively with the analytical methods used were descriptive statistics and multiple regression analysis. To test the hypothesis, the t test and Sobel test were carried out. The research results show that work culture and competency development have a direct and indirect effect on self-confidence and job satisfaction. So that self-confidence is able to mediate the influence of work culture and competency development on job satisfaction.